Sugarcane trash management assessed by the interaction of yield with soil properties - Dalchiavon, Flávio Carlos; Carvalho, Morel De Passos E [UNESP]; Montanari, Rafael [UNESP]; Andreotti, Marcelo [UNESP]; Dal Bem, Edjair Augusto [UNESP] (Sociedade Brasileira de Ciência do Solo, 2013)
Currently, sugarcane plays an important global role, particularly with a view to alternative energy sources. Thus, in a sugarcane field of the mill Vale do Paraná S/A Álcool e Açúcar, Rubineia, São Paulo State, managed under two green cane harvest systems (cane trash left on and cane trash removed from the soil), Pearson and spatial correlations between the sugarcane yield (variety RB855035 in the third cut) and soil physical and chemical properties were studied to identify the property best correlated with stalk yield and the best harvest method. For this purpose, two geostatistical grids (121 sampling points on 1.30 ha) were installed on a eutrophic Red Argisol (homogeneous slope of 0.065 m m-1), in 2011, to determine the properties: stalk yield and sugarcane plant population, and soil resistance to penetration, gravimetric moisture, bulk density, and carbon stock, in the layers 0-0.20 and 0.20-0.40 m. The data were analyzed by descriptive, linear correlation and geostatistical analysis. In both treatments, the property stand density was best correlated with sugarcane yield (r = 0.725 in the trash mulching treatment - TM and r = 0.769 in the trash removal treatment - TR). However, in relation to the soil properties, bulk density (0-0.20 m) was best correlated (r = 0.305 in TM, r = 0.211 in TR). Similarly, from the spatial point of view, stand density was the property that best explained the sugarcane yield. However, in the TM treatment the density (0.20-0.40 m) was the only soil property spatially correlated with stalk yield. The carbon stock in the soil of the TM was 11.5 % higher than in the TR treatment. Results of the TM treatment were best, also with regard to soil management and conservation.

Atualmente, a cultura da cana-de-açúcar desempenha importante papel no cenário mundial, sobretudo ao aspecto relacionado às fontes energéticas alternativas. Assim, em um talhão de cana-de-açúcar na Usina Vale do Paraná S/A Álcool e Açúcar, Rubineia, SP, manejado sob duas formas de colheita da cana crua, com palhada (COP) e sem palhada (SEP) sobre o solo, foram estudadas as correlações Pearson e espacial entre a produtividade da cana-de-açúcar (variedade RB855035, em seu terceiro corte) e as propriedades físico-químicas do solo, objetivando verificar aquele que possui a melhor correlação com essa produtividade, assim como o melhor método de colheita. Para tanto, foram instaladas duas malhas geoestatísticas (1,30 ha e 121 pontos amostrais cada) em um Argissolo Vermelho eutrófico (declive homogêneo de 0,065 m m-1), no ano de 2011. Os atributos avaliados foram: produtividade de colmos de cana-de-açúcar, população de plantas, resistência do solo à penetração, umidade gravimétrica, densidade e estoque de carbono do solo, nas profundidades de 0-0,20 e 0,20-0,40 m. Realizaram-se as análises descritiva, correlações lineares e geoestatística dos dados. Em ambos os tratamentos, a população de plantas apresentou a melhor correlação de Pearson (r = 0,725** em COP; r = 0,769** em SEP), com a produtividade da cana-de-açúcar. Entretanto, em relação ao solo, a densidade (0-0,20 m) teve a melhor correlação (r = 0,305** em COP; r = 0,211* em SEP). Da mesma forma, do ponto de vista espacial, a população de plantas melhor explicou a produtividade da cana-de-açúcar. Contudo, a densidade (0,20-0,40 m) do tratamento com palhada foi a única propriedade do solo que apresentou correlação espacial com a produtividade de colmos. O estoque de carbono do solo para o tratamento com palhada foi 11,5 % superior ao sem palhada. O tratamento com palhada foi o que possibilitou os melhores resultados, inclusive no que se refere ao manejo e à conservação do solo.
Manejo da palhada de cana-de-açúcar avaliado pela interação da produtividade com propriedades do solo
Keywords: produção sucroalcooleira; manejo e conservação do solo; sustentabilidade ambiental; mapas de krigagem; Saccharum officinarum L; sugar and ethanol production; soil management and conservation; environmental sustainability; kriging maps; Saccharum officinarum L.